Hysteresis Phenomena and Their Modelling in Martensitic Transformation Thermodynamics - O. A. Likhachev, Yu. M. Koval (Успехи физики металлов, 2015)
In the present review paper, we show that a successful description of the irreversible evolution of macroscopic variables during the martensitic transformations caused by hysteresis is possible with using a special type of differential equations with the temperature-dependent coefficient depending only on the main hysteresis loop shape. These equations make it possible to predict the macroscopic volume fraction evolution for an arbitrary temperature change process including the partial subloops. For this aim, one should know only the information about the temperature behaviour for transformation paths representing the main hysteresis loop. The present model is practically applied and experimentally confirmed for martensitic transformation in CuZnAl alloy.